Polyester antibacterial fabric and preparation method thereof
Patent Information
- Application Number
- CN202611171242.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-04
AI Technical Summary
[0002]随着纺织表面改性技术的不断演进,涤纶织物多功能化处理的复杂性显著增加;现有的改性处理技术在抗菌活性成分的稳定固载和多重抗菌机制协同方面存在技术缺陷
[0023] This invention exposes hydrophilic groups in polyester fabrics through sodium hydroxide pretreatment, thereby making them more suitable for use in textiles. The stable growth of nanosheet arrays provides binding sites; at the same time, the adhesion of dopamine hydrochloride is used to firmly anchor the core-shell nanoparticles to the fabric surface and provide reaction sites for the grafting of chitosan quaternary ammonium salt; this preparation method enhances the loading stability of antibacterial components on the fiber surface and improves the wash resistance and antibacterial properties of the fabric.
Smart Images

Figure CN122707377B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional textile materials and surface modification, specifically to a polyester antibacterial fabric and its preparation method. Background Technology
[0002] With the continuous evolution of textile surface modification technology, the complexity of multifunctional treatment of polyester fabrics has increased significantly; existing modification technologies have technical deficiencies in terms of stable immobilization of antibacterial active ingredients and synergistic effects of multiple antibacterial mechanisms.
[0003] Currently, polyester fabrics are generally treated with traditional impregnation or coating processes, which attach single antibacterial agents such as silver nanoparticles and quaternary ammonium salts to the fabric surface through physical adsorption or simple chemical cross-linking. However, traditional antibacterial finishing methods rely on the release of single active components and their weak electrical binding with the fiber surface, making it difficult for effective antibacterial components to form a stable interfacial anchor. Although these methods can provide short-term antibacterial protection for fabrics, they usually have low wash resistance, and effective antibacterial components are easily lost during washing, resulting in a significant decrease in antibacterial performance with increasing washing cycles. Furthermore, they cannot achieve the synergistic effect of multiple mechanisms such as contact killing, ion slow release, and photocatalysis.
[0004] Therefore, how to improve the load stability of antibacterial components in polyester fabrics while taking into account both rapid sterilization and long-lasting antibacterial properties has become an urgent problem to be solved in this field. Summary of the Invention
[0005] To achieve the above objectives, this invention proposes a polyester antibacterial fabric and its preparation method that can improve the loading stability of antibacterial components on the fiber surface and simultaneously achieve rapid sterilization and long-lasting antibacterial properties; the specific technical solution is as follows:
[0006] A method for preparing a polyester antibacterial fabric includes the following steps:
[0007] Step 1: Preparation Core-shell nanoparticles: prepared by chemical reduction method Nanoparticle sol was sequentially coated with a mesoporous silica layer and a titanium dioxide layer to obtain... Core-shell nanoparticles;
[0008] Step 2, Pretreatment of polyester fabric: Immerse the polyester fabric in a mixed solution containing sodium hydroxide and zinc acetate for alkali reduction pretreatment, wash and dry;
[0009] Step 3: Hydrothermal Growth Nanosheet array: The polyester fabric treated in step two was placed in a precursor solution containing zinc salt and morphology control agent, with the pH adjusted to 8.5-10.5, for hydrothermal reaction, resulting in in-situ growth of nanosheets on the fabric surface. The nanosheet array was removed, washed, and dried.
[0010] Step 4, Polydopamine Co-deposition and Particle Anchoring: Immerse the fabric obtained in Step 3 in a solution containing dopamine hydrochloride and the aforementioned... In a weakly alkaline buffer solution of core-shell nanoparticles, polydopamine and the core-shell nanoparticles are co-deposited on the surface of a fabric under oxygen-containing conditions.
[0011] Step 5, Surface functionalization modification: Immerse the fabric obtained in step 4 in an aqueous solution of chitosan quaternary ammonium salt, wash and dry to obtain polyester antibacterial fabric.
[0012] Preferably, in step one, the... The preparation method of core-shell nanoparticles includes: ... After mixing anhydrous ethanol thoroughly with the nanoparticle sol, hexadecyltrimethylammonium bromide was added to achieve a concentration of 1-5 mmol / L. Tetraethyl orthosilicate and ammonia were then added dropwise, with tetraethyl orthosilicate added at 0.1-1 mL / 100 mL of sol and 28% ammonia at 0.8-2.0 mL / 100 mL of sol. After hydrolysis and condensation, the mixture was collected by centrifugation and washed with an ethanol solution containing hydrochloric acid under reflux to obtain nanoparticles with a mesopore size of 2-5 nm. Nanoparticles;
[0013] The Nanoparticles were dispersed in a mixed solvent of anhydrous ethanol and isopropanol containing tetrabutyl titanate (0.01-0.05 mol / L). An ethanol solution containing deionized water and ammonia was added dropwise for sol-gel coating. After centrifugation, washing, and vacuum drying, the nanoparticles were calcined in an inert gas atmosphere at 400-450℃ for 2-4 hours, forming a titanium dioxide layer on the outermost layer, thus obtaining the desired product. Core-shell nanoparticles.
[0014] Preferably, a chemical reduction method is used to prepare the product. In the nanoparticle sol step, silver nitrate is reduced using sodium borohydride as a reducing agent under ice bath conditions to obtain the desired product. Nanoparticle sol.
[0015] Preferably, in step two, the concentration of sodium hydroxide is 0.05-0.5 mol / L, the concentration of zinc acetate is 0.01-0.1 mol / L, the temperature of the heating and impregnation treatment is 50-70℃, and the time is 20-40 min; the solvent of the mixed solution is ethanol and water, and the volume ratio of ethanol to water is 7:3 to 9:1; the drying temperature is 50-70℃, and the time is 10-120 min.
[0016] Preferably, in step three, the precursor solution further includes a morphology control agent and sodium dodecyl sulfate, and the concentration of zinc salt is 0.01-0.1 mol / L, the concentration of sodium dodecyl sulfate is 0.001-0.005 mol / L, the hydrothermal reaction temperature is 75-110℃, and the time is 2-6 h; the zinc salt is zinc nitrate or zinc sulfate; the morphology control agent is sodium citrate or disodium hydrogen phosphate, and the molar ratio of the morphology control agent to the zinc salt is 1:5 to 1:1; the pH value is adjusted using ammonia water; the washing method is alternating soaking and washing with deionized water and anhydrous ethanol.
[0017] Preferably, in step four, the weakly alkaline buffer solution has a pH of 8.0-9.0 and a concentration of 10-50 mmol / L, and the dopamine hydrochloride concentration is 1-3 mg / mL. The concentration of core-shell nanoparticles is 2-5 mg / mL, the reaction temperature is 20-30℃, and the reaction time is 12-24 h; the buffer solution is a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution; the co-deposition is an oscillating reaction.
[0018] Preferably, in step five, the mass fraction of the chitosan quaternary ammonium salt aqueous solution is 0.5%-2.0%, the reaction temperature is 40-60℃, and the reaction time is 2-4h; the molecular weight of the chitosan quaternary ammonium salt is 50,000-200,000.
[0019] Preferably, in step three, the... Nanosheet arrays The nanosheets have a thickness of 10-60 nm and a lateral dimension of 200-1200 nm.
[0020] Preferably, the The outermost titanium dioxide layer of the core-shell nanoparticles is 10-30 nm thick and is anatase.
[0021] Preferably, the polyester antibacterial fabric provided by the present invention is prepared by the above-described preparation method.
[0022] The beneficial effects of this invention are as follows:
[0023] This invention exposes hydrophilic groups in polyester fabrics through sodium hydroxide pretreatment, thereby making them more suitable for use in textiles. The stable growth of nanosheet arrays provides binding sites; at the same time, the adhesion of dopamine hydrochloride is used to firmly anchor the core-shell nanoparticles to the fabric surface and provide reaction sites for the grafting of chitosan quaternary ammonium salt; this preparation method enhances the loading stability of antibacterial components on the fiber surface and improves the wash resistance and antibacterial properties of the fabric.
[0024] This invention grows an array of interlaced nanosheets on the surface of fabric via a hydrothermal reaction, increasing surface roughness and providing contact sterilization. Simultaneously, it introduces core-shell nanoparticles containing silver and mesoporous silica internally and titanium dioxide externally. These nanoparticles not only achieve stable and sustained ion release through unsealed mesoporous channels but also enhance bacterial adsorption in conjunction with the surface-grafted chitosan quaternary ammonium salt layer. Through photogenerated carrier separation and confined sustained ion release at the heterojunction interface, a synergistic effect of multiple mechanisms—contact sterilization, ion release, and photocatalysis—is achieved, thus balancing both sterilization and bacteriostatic properties. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] Example 1:
[0027] This embodiment provides a polyester antibacterial fabric, specifically including the following steps:
[0028] S1, Preparation Core-shell nanoparticles: 50 mL of a 1 mmol / L silver nitrate aqueous solution was placed in an ice bath and stirred. 10 mL of a 2 mmol / L sodium borohydride aqueous solution was added dropwise, and stirring was continued for 30 min. Silver nitrate was reduced using sodium borohydride to obtain nanoparticles with a particle size of 15 nm. Nanoparticle sol; hexadecyltrimethylammonium bromide was added to the sol to make its concentration 3 mmol / L;
[0029] Add 0.5 mL of tetraethyl orthosilicate and 1.0 mL of 28% ammonia solution per 100 mL of sol for hydrolysis and polycondensation. Collect the product by centrifugation. Wash the collected product under reflux in an ethanol solution containing hydrochloric acid to remove the template agent, yielding a mesoporous product with a pore size of 3 nm. 20nm layer thickness Nanoparticles;
[0030] Will Nanoparticles were dispersed in a mixed solvent of anhydrous ethanol and isopropanol. The concentration of tetrabutyl titanate was controlled at 0.03 mol / L. A sol-gel coating was achieved by adding 20 mL of ethanol solution containing 0.5 mL of deionized water and 0.2 mL of 28% ammonia. After centrifugation, washing, and vacuum drying, the nanoparticles were calcined at 450 °C for 3 h under an inert gas atmosphere such as nitrogen or argon to obtain an outer titanium dioxide layer with a thickness of 15 nm. Core-shell nanoparticles, titanium dioxide ( It is anatase type; the core-shell nanoparticles serve as the core component for subsequent antibacterial activity, providing dual antibacterial effects of photocatalysis and silver ion slow release;
[0031] S2. Polyester fabric pretreatment: Take a 10cm×10cm polyester fabric and immerse it in a mixed solution of ethanol and water containing 0.1mol / L sodium hydroxide and 0.02mol / L zinc acetate (ethanol to water volume ratio 8:2). Treat at 60℃ for 30min. After treatment, remove the fabric, wash with deionized water until neutral, and dry at 60℃ for 30min to obtain the pretreated fabric. The surface of this pretreated fabric exposes a large number of hydrophilic groups, which are beneficial for subsequent processing. The stable growth of nanosheet arrays provides binding sites;
[0032] S3, hydrothermal growth Nanosheet array; using deionized water as solvent, a precursor solution containing 0.05 mol / L zinc nitrate, 0.02 mol / L sodium citrate and 0.002 mol / L sodium dodecyl sulfate was prepared, and the pH was adjusted to 9.5 with ammonia; the pretreated fabric was placed vertically in a polytetrafluoroethylene-lined reactor, the precursor solution was added, and the reaction was carried out at 95°C for 4 hours;
[0033] After the reaction was complete, the fabric was removed and washed alternately with deionized water and anhydrous ethanol, then dried to obtain a surface with interlaced layers. Modified polyester fabric with nanosheet array; the resulting The nanosheets are 30 nm thick and have a lateral dimension of 600 nm. This modified polyester fabric has... The nanosheet array increases surface roughness and provides a mechanically disruptive effect for contact sterilization;
[0034] S4, polydopamine co-deposited and anchored Core-shell nanoparticles; modified polyester fabric was immersed in a tris(hydroxymethyl)aminomethane-hydrochloric acid (Tris-HCl) buffer solution with a pH of 8.5 and a concentration of 20 mM; the concentration of dopamine hydrochloride was 2 mg / mL. The concentration of core-shell nanoparticles was 3 mg / mL;
[0035] The fabric was shaken at room temperature (25°C) for 16 hours under open air conditions. After the reaction, the fabric was removed and thoroughly washed with deionized water to obtain the co-deposited modified fabric. This co-deposited modified fabric adheres to the surface through the adhesion of dopamine. Core-shell nanoparticles are firmly anchored on the fabric surface and provide reaction sites for subsequent grafting of chitosan quaternary ammonium salts;
[0036] S5. Surface functionalization modification of chitosan quaternary ammonium salt: The co-deposited modified fabric was immersed in an aqueous solution of chitosan quaternary ammonium salt with a molecular weight of 100,000 at 1.0 wt% and shaken at 50℃ for 3 hours. After the reaction, it was thoroughly washed with deionized water and dried at 60℃ to obtain polyester antibacterial fabric. The chitosan quaternary ammonium salt layer on the surface of the polyester antibacterial fabric enhanced the adsorption of negatively charged bacteria and improved the overall antibacterial efficiency.
[0037] Example 2:
[0038] This embodiment provides a polyester antibacterial fabric, specifically including the following steps:
[0039] S1, Preparation Core-shell nanoparticles were prepared by stirring 40 mL of a 0.5 mmol / L silver nitrate aqueous solution in an ice bath, then adding 8 mL of a 1.5 mmol / L sodium borohydride aqueous solution dropwise while stirring for 20 min. The silver nitrate was reduced using sodium borohydride to obtain the desired nanoparticles. Nanoparticle sol;
[0040] Hexadecyltrimethylammonium bromide was added to the sol to achieve a concentration of 2 mmol / L; 0.3 mL of tetraethyl orthosilicate was added per 100 mL of sol, followed by 0.8 mL of 28% ammonia solution for hydrolysis and polycondensation. The product was collected by centrifugation; after reflux washing with an ethanol solution containing hydrochloric acid, a mesoporous pore size of 2 nm was obtained. Nanoparticles;
[0041] This Nanoparticles were dispersed in a mixed solvent of anhydrous ethanol and isopropanol, with a tetrabutyl titanate concentration of 0.02 mol / L. A 15 mL ethanol solution containing 0.4 mL deionized water and 0.1 mL of 28% ammonia was added dropwise for coating. After centrifugation, washing, and vacuum drying, the nanoparticles were calcined at 420℃ for 2 h to obtain an outer titanium dioxide layer with a thickness of 12 nm. Core-shell nanoparticles; these core-shell nanoparticles serve as the core component for subsequent antibacterial activity, providing dual antibacterial effects through photocatalysis and sustained release of silver ions;
[0042] S2. Polyester fabric pretreatment: Take a 10cm×10cm polyester fabric and immerse it in a mixed solution of ethanol and water containing 0.05mol / L sodium hydroxide and 0.01mol / L zinc acetate (ethanol to water volume ratio 9:1). Treat at 50℃ for 20min. After removal, wash until neutral and dry at 50℃ for 20min to obtain the pretreated fabric. The surface of this pretreated fabric exposes a large number of hydrophilic groups, which are beneficial for subsequent processing. The stable growth of nanosheet arrays provides binding sites;
[0043] S3, hydrothermal growth Nanosheet array; a precursor solution containing 0.03 mol / L zinc sulfate, 0.01 mol / L disodium hydrogen phosphate, and 0.001 mol / L sodium dodecyl sulfate was prepared, and the pH was adjusted to 8.8 with ammonia; the pretreated fabric was placed in a reaction vessel and reacted at 80℃ for 3 h; after the reaction, the fabric was alternately soaked and washed with deionized water and anhydrous ethanol and dried to obtain the grown nanosheet array; Modified polyester fabric with nanosheet array; the resulting The nanosheets are 50 nm thick and have a lateral dimension of 900 nm. This modified polyester fabric has... The nanosheet array increases surface roughness and provides a mechanically disruptive effect for contact sterilization;
[0044] S4, polydopamine co-deposited and anchored Core-shell nanoparticles; modified polyester fabric was immersed in Tris-HCl buffer solution with pH 8.5 and a concentration of 10 mM; dopamine hydrochloride concentration was 1 mg / mL. The core-shell nanoparticles were concentrated at 2 mg / mL and shaken at room temperature (25°C) for 12 hours under open air conditions. After washing, a co-deposited modified fabric was obtained. This co-deposited modified fabric adhered to the substrate through the adhesion of dopamine. Core-shell nanoparticles are firmly anchored on the fabric surface and provide reaction sites for subsequent grafting of chitosan quaternary ammonium salts;
[0045] S5. Surface functionalization modification of chitosan quaternary ammonium salt: The co-deposited modified fabric was immersed in a 0.5wt% aqueous solution of chitosan quaternary ammonium salt with a molecular weight of 50,000, and oscillated at a constant temperature of 40℃ for 2 hours. After washing and drying, polyester antibacterial fabric was obtained. The chitosan quaternary ammonium salt layer on the surface of the polyester antibacterial fabric enhanced the adsorption of negatively charged bacteria and improved the overall antibacterial efficiency.
[0046] Example 3:
[0047] This embodiment provides a polyester antibacterial fabric, specifically including the following steps:
[0048] S1, Preparation Core-shell nanoparticles were prepared by stirring 60 mL of a 2 mmol / L silver nitrate aqueous solution in an ice bath, then adding 15 mL of a 3 mmol / L sodium borohydride aqueous solution dropwise while stirring for 40 min. The silver nitrate was then reduced using sodium borohydride. Nanoparticle sol;
[0049] Hexadecyltrimethylammonium bromide was added to the sol to achieve a concentration of 4 mmol / L; 0.8 mL of tetraethyl orthosilicate was added per 100 mL of sol, followed by 1.5 mL of 28% ammonia solution for hydrolysis and polycondensation. The product was collected by centrifugation; after washing with ethanol solution containing hydrochloric acid under reflux, a mesoporous pore size of 2 nm was obtained. Nanoparticles;
[0050] The tetrabutyl titanate was dispersed in a mixed solvent of anhydrous ethanol and isopropanol at a concentration of 0.04 mol / L. A 25 mL ethanol solution containing 0.8 mL of deionized water and 0.3 mL of 28% ammonia was added dropwise for coating. After centrifugation, washing, and vacuum drying, the mixture was calcined at 430 °C for 4 h to obtain an outer titanium dioxide layer with a thickness of approximately 20 nm. Core-shell nanoparticles;
[0051] S2. Pretreatment of polyester fabric: Take a 10cm×10cm polyester fabric and immerse it in a mixed solution of ethanol and water containing 0.2mol / L sodium hydroxide and 0.04mol / L zinc acetate. The volume ratio of ethanol to water is 7:3. Treat at 65℃ for 35min. After taking it out, wash it until neutral and dry at 65℃ for 60min.
[0052] S3, hydrothermal growth Nanosheet array; a precursor solution containing 0.08 mol / L zinc nitrate, 0.04 mol / L sodium citrate, and 0.003 mol / L sodium dodecyl sulfate was prepared, and the pH was adjusted to 10.0 with ammonia; the pretreated fabric was placed in a reaction vessel and reacted at 110℃ for 6 h; after the reaction, the fabric was alternately soaked and washed with deionized water and anhydrous ethanol and then dried; the resulting... The nanosheets are approximately 20 nm thick and have a lateral dimension of approximately 450 nm.
[0053] S4, polydopamine co-deposited and anchored Core-shell nanoparticles; the fabric obtained in step S3 was immersed in Tris-HCl buffer solution with a pH of 8.5 and a concentration of 30 mM; the concentration of dopamine hydrochloride was 2.5 mg / mL. The core-shell nanoparticles were concentrated at 4 mg / mL and shaken at room temperature for 20 h under micro-air bubbling conditions; after washing, a co-deposited modified fabric was obtained.
[0054] S5. Surface functionalization modification of chitosan quaternary ammonium salt: The fabric obtained in step S4 is immersed in a 1.5 wt% aqueous solution of chitosan quaternary ammonium salt with a molecular weight of 150,000, and shaken at a constant temperature of 55°C for 3 hours. After washing and drying, polyester antibacterial fabric is obtained.
[0055] Example 4:
[0056] This embodiment provides a polyester antibacterial fabric, specifically including the following steps:
[0057] S1, Preparation Core-shell nanoparticles were prepared by stirring 80 mL of a 2.5 mmol / L silver nitrate aqueous solution in an ice bath, then adding 20 mL of a 4 mmol / L sodium borohydride aqueous solution dropwise while stirring for 50 min. The silver nitrate was then reduced with sodium borohydride to obtain the desired nanoparticles. Nanoparticle sol;
[0058] Hexadecyltrimethylammonium bromide was added to the sol to achieve a concentration of 5 mmol / L; 1.0 mL of tetraethyl orthosilicate was added per 100 mL of sol, followed by 2.0 mL of 28% ammonia solution for hydrolysis and polycondensation. The product was collected by centrifugation; after washing with ethanol solution containing hydrochloric acid under reflux, a mesoporous pore size of 2 nm was obtained. Nanoparticles;
[0059] The tetrabutyl titanate was dispersed in a mixed solvent of anhydrous ethanol and isopropanol at a concentration of 0.05 mol / L. A 30 mL ethanol solution containing 1.0 mL deionized water and 0.4 mL of 28% ammonia was added dropwise for coating. After centrifugation, washing, and vacuum drying, the mixture was calcined at 400℃ for 3 h to obtain an outer titanium dioxide layer with a thickness of 30 nm. Core-shell nanoparticles; these core-shell nanoparticles serve as the core component for subsequent antibacterial activity, providing dual antibacterial effects through photocatalysis and sustained release of silver ions;
[0060] S2. Polyester fabric pretreatment: Take a 10cm×10cm polyester fabric and immerse it in a mixed solution of ethanol and water containing 0.5mol / L sodium hydroxide and 0.1mol / L zinc acetate (ethanol to water volume ratio 7:3). Treat at 70℃ for 40min. After removal, wash until neutral and dry at 70℃ for 90min to obtain the pretreated fabric. The surface of this pretreated fabric exposes a large number of hydrophilic groups, which are beneficial for subsequent processing. The stable growth of nanosheet arrays provides binding sites;
[0061] S3, hydrothermal growth Nanosheet array; a precursor solution containing 0.10 mol / L zinc nitrate, 0.05 mol / L sodium citrate, and 0.005 mol / L sodium dodecyl sulfate was prepared, and the pH was adjusted to 10.0 with ammonia; the pretreated fabric was placed in a reaction vessel and reacted at 110℃ for 6 h; after the reaction, the fabric was alternately soaked and washed with deionized water and anhydrous ethanol and dried to obtain the grown nanosheet array; Modified polyester fabric with nanosheet array; the resulting The nanosheets are 12 nm thick and 300 nm in lateral dimension. This modified polyester fabric has... The nanosheet array increases surface roughness and provides a mechanically disruptive effect for contact sterilization;
[0062] S4, polydopamine co-deposited and anchored Core-shell nanoparticles; modified polyester fabric was immersed in Tris-HCl buffer solution with pH 8.5 and a concentration of 50 mM; dopamine hydrochloride concentration was 3 mg / mL. The nanoparticle concentration was 5 mg / mL, and the mixture was shaken at room temperature (25°C) for 24 hours under micro-air bubbling conditions. After washing, a co-deposited modified fabric was obtained. This co-deposited modified fabric adheres to the substrate through the adhesion of dopamine. Core-shell nanoparticles are firmly anchored on the fabric surface and provide reaction sites for subsequent grafting of chitosan quaternary ammonium salts;
[0063] S5. Surface functionalization modification of chitosan quaternary ammonium salt: The co-deposited modified fabric was immersed in a 2.0 wt% aqueous solution of chitosan quaternary ammonium salt with a molecular weight of 200,000, and oscillated at 60°C for 4 hours. After washing and drying, polyester antibacterial fabric was obtained. The chitosan quaternary ammonium salt layer on the surface of the polyester antibacterial fabric enhanced the adsorption of negatively charged bacteria and improved the overall antibacterial efficiency.
[0064] Comparative Example 1:
[0065] The difference between this comparative example and Example 1 is that step S2 is omitted, and the sodium hydroxide and zinc acetate pretreatment is not performed. The other operating steps and process parameters are exactly the same as those in the embodiments of the present invention.
[0066] Comparative Example 2:
[0067] The difference between this comparative example and Example 1 is that step S3 is omitted, and hydrothermal growth is not performed on the fabric surface. The nanosheet array, other operating steps and process parameters are exactly the same as those in the embodiments of this invention.
[0068] Comparative Example 3:
[0069] The difference between this comparative example and Example 1 is that step S4 is omitted, and polydopamine co-deposition and... The nanoparticle anchoring treatment, along with other operating steps and process parameters, is exactly the same as the implementation method of this invention.
[0070] Comparative Example 4:
[0071] The difference between this comparative example and Example 1 is that: in step S1, no construction is performed. Mesoporous layer, directly Nanoparticle coating Outer layer, made The nanoparticles are used for subsequent processing, and other operating steps and process parameters are exactly the same as those in the embodiments of this invention.
[0072] Comparative Example 5:
[0073] The difference between this comparative example and Example 1 is that step S1 does not include... Outer layer, only prepared The nanoparticles are used for subsequent processing, and other operating steps and process parameters are exactly the same as those in the embodiments of this invention.
[0074] Comparative Example 6:
[0075] The difference between this comparative example and Example 1 is that step S5 is omitted and the chitosan quaternary ammonium salt surface functionalization modification is not performed. Other operation steps and process parameters are exactly the same as those in the embodiments of the present invention.
[0076] Performance testing and data sheets:
[0077] In this invention, the nanoscale morphology and size were observed and measured using scanning electron microscopy and high-resolution transmission electron microscopy; the molecular weight of chitosan quaternary ammonium salt was determined using gel permeation chromatography; the static water droplet contact angle on the fabric surface was measured using a contact angle meter; the antibacterial performance was tested according to GB / T20944.3-2008, with Escherichia coli as the test species; the wash resistance was determined by washing the fabric 50 times continuously with alkaline water according to the GB / T8629-2017 standard, followed by measuring the antibacterial rate using the same method; and the hydrophilicity of the fabric surface was characterized using the static water droplet contact angle.
[0078] Table 1. Performance test results of fabrics in each embodiment and comparative example.
[0079] Example 1 14° 99.8% 99.9% 99.8% Example 2 19° 99.3% 99.7% 99.4% Example 3 16° 99.5% 99.8% 99.6% Example 4 11° 99.6% 99.8% 99.3% Comparative Example 1 76° 90.4% 93.8% 58.6% Comparative Example 2 43° 95.2% 98.1% 91.4% Comparative Example 3 28° 92.8% 94.6% 70.3% Comparative Example 4 18° 98.9% 97.2% 82.5% Comparative Example 5 22° 97.8% 96.5% 94.8% Comparative Example 6 37° 96.9% 97.4% 92.2%
[0080] As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, after omitting the pretreatment step, the antibacterial rate at 30 min, 24 h, and after washing all decreased significantly, while the contact angle increased significantly. Without the mild alkali reduction treatment with sodium hydroxide, the ester bond etching on the polyester surface was insufficient, resulting in less exposure of hydrophilic groups. Seed crystals are difficult to form stably and embed into the fiber surface; this change will affect subsequent... As the growth density of the nanosheet array decreases, the loading of polydopamine and core-shell particles also decreases, resulting in a reduction of active components on the fabric surface that can participate in antibacterial activity. At the same time, the anchoring strength is insufficient, so the antibacterial rate decreases significantly after washing.
[0081] As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, the following was omitted: After the nanosheet array growth step, the rapid antibacterial performance, long-lasting antibacterial performance, and post-wash antibacterial performance all decreased; the fabric surface lacked interlaced layers. Micro-nano structures reduce the mechanical damage during contact sterilization. and The corresponding interface synergy cannot be formed between them, and the separation efficiency of photogenerated carriers decreases; at the same time, the rough structure of the fabric surface is weakened, the adhesion area of the polydopamine co-deposited layer is reduced, resulting in a decrease in the amount of fixation of the subsequent composite layer, so the overall antibacterial performance is lower than that of Example 1.
[0082] As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, the polydopamine co-deposition and... After the anchoring step, all antibacterial and wash resistance indicators decreased significantly; the polydopamine layer provides an adhesion interface for the core-shell particles and a subsequent covalent binding site for the chitosan quaternary ammonium salt; without this layer, , and The components failed to be fixed on the fabric surface, and the fabric mainly relied on Its own function is to release slowly in the dark. Neither sterilization nor photocatalytic sterilization can be fully utilized; at the same time, the lack of quinone reaction sites between chitosan quaternary ammonium salt and the substrate reduces the stability of the surface polyelectrolyte layer, resulting in a significant decrease in antibacterial rate after washing.
[0083] As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, with Alternative Afterwards, the antibacterial rate at 30 minutes was close to that of Example 1, but the antibacterial rate at 24 hours and after washing decreased; lacking After the mesoporous layer, There is a lack of stable confined diffusion channels between the device and the external medium. It releases faster and can maintain a high level of sterilization for a short time, so the rapid decrease in antibacterial rate is not significant; however, this structure is not conducive to sustained slow release, and the silver component is more easily lost during washing, resulting in a decrease in long-lasting antibacterial performance and wash resistance.
[0084] As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, the omission of... After the outer layer is applied, the rapid antibacterial rate, 24-hour antibacterial rate, and antibacterial rate after washing all decrease; anatase type is lacking. After the outer layer, the photocatalytic activity of the composite particles weakens. and Interfacial synergy no longer exists, and the formation of reactive oxygen species decreases under visible and ultraviolet light conditions; although It can still provide a certain amount It has a sustained-release effect, but this effect mainly corresponds to sterilization in the dark and cannot replace the photocatalytic part. Therefore, its overall antibacterial performance is lower than that of Example 1.
[0085] As can be seen from the comparison of the test results of Example 1 and Comparative Example 6 in Table 1, omitting the surface functionalization modification of chitosan quaternary ammonium salt resulted in an increased contact angle and a decrease in rapid antibacterial performance, 24-hour antibacterial performance, and wash resistance. The chitosan quaternary ammonium salt molecular chains carry a positive quaternary ammonium charge, which enhances the adsorption of negatively charged bacterial membranes, making it easier for bacteria to contact them. The array, polydopamine layer and photocatalytic active region; without chitosan quaternary ammonium salt, the electro-adsorption on the fabric surface is weakened, the probability of bacteria contacting the active site is reduced, and the hydrophilicity is reduced, which is not conducive to the contact between the active component in the liquid phase and the bacteria. Therefore, the antibacterial efficiency and the retention rate after washing are both lower than those in Example 1.
[0086] The test results from Examples 1 to 4 show that, within the scope defined by the technical solution of this invention, adjustments can be made... Aperture, The thickness, hydrothermal growth conditions, and amount of chitosan quaternary ammonium salt can all be adjusted to obtain fabrics with high antibacterial rate and excellent washability.
[0087] Example 2 uses lower boundary parameters. The nanosheet growth density and surface functional layer loading are relatively low, so the various indicators are slightly lower; Example 3 will... The aperture is controlled within a small range. It has a slow release rate, stable and long-lasting antibacterial properties, and a rapid decrease in antibacterial rate;
[0088] Example 4: Increasing the concentration of chitosan quaternary ammonium salt and enhancing... The array growth degree is excellent, the surface hydrophilicity and rapid antibacterial properties are excellent, but the antibacterial rate tends to decrease after washing due to the high content of polyelectrolytes in the outer layer. Overall results show that the preparation method can stably obtain polyester antibacterial fabrics with rapid antibacterial, continuous antibacterial and wash-resistant properties.
[0089] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a polyester antibacterial fabric, characterized in that, Includes the following steps: Step 1: Preparation Core-shell nanoparticles: prepared by chemical reduction method Nanoparticle sol was sequentially coated with a mesoporous silica layer and a titanium dioxide layer to obtain... Core-shell nanoparticles; Step 2, Pretreatment of polyester fabric: Immerse the polyester fabric in a mixed solution containing sodium hydroxide and zinc acetate for alkali reduction pretreatment, wash and dry; Step 3: Hydrothermal Growth Nanosheet array: The polyester fabric treated in step two was placed in a precursor solution containing zinc salt and morphology control agent, with the pH adjusted to 8.5-10.5, for hydrothermal reaction, resulting in in-situ growth of nanosheets on the fabric surface. The nanosheet array was removed, washed, and dried. Step 4, Polydopamine Co-deposition and Particle Anchoring: Immerse the fabric obtained in Step 3 in a solution containing dopamine hydrochloride and the aforementioned... In a weakly alkaline buffer solution of core-shell nanoparticles, polydopamine and the core-shell nanoparticles are co-deposited on the surface of a fabric under oxygen-containing conditions. Step 5, Surface functionalization modification: Immerse the fabric obtained in step 4 in an aqueous solution of chitosan quaternary ammonium salt, wash and dry to obtain polyester antibacterial fabric; In step one, the The preparation method of core-shell nanoparticles includes: ... After mixing anhydrous ethanol thoroughly with the nanoparticle sol, hexadecyltrimethylammonium bromide was added to achieve a concentration of 1-5 mmol / L. Tetraethyl orthosilicate and ammonia were then added dropwise, with tetraethyl orthosilicate added at 0.1-1 mL / 100 mL of sol and 28% ammonia at 0.8-2.0 mL / 100 mL of sol. After hydrolysis and condensation, the mixture was collected by centrifugation and washed with an ethanol solution containing hydrochloric acid under reflux to obtain nanoparticles with a mesopore size of 2-5 nm. Nanoparticles; The Nanoparticles were dispersed in a mixed solvent of anhydrous ethanol and isopropanol containing tetrabutyl titanate (0.01-0.05 mol / L). An ethanol solution containing deionized water and ammonia was added dropwise for sol-gel coating. After centrifugation, washing, and vacuum drying, the nanoparticles were calcined in an inert gas atmosphere at 400-450℃ for 2-4 hours, forming a titanium dioxide layer on the outermost layer, thus obtaining the desired product. Core-shell nanoparticles.
2. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, Prepared by chemical reduction method In the nanoparticle sol step, silver nitrate is reduced using sodium borohydride as a reducing agent under ice bath conditions to obtain the desired product. Nanoparticle sol.
3. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, In step two, the concentration of sodium hydroxide is 0.05-0.5 mol / L, the concentration of zinc acetate is 0.01-0.1 mol / L, the temperature of the heating and impregnation treatment is 50-70℃, and the time is 20-40 min; the solvent of the mixed solution is ethanol and water, and the volume ratio of ethanol to water is 7:3 to 9:1; the drying temperature is 50-70℃, and the time is 10-120 min.
4. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, In step three, the precursor solution also includes a morphology control agent and sodium dodecyl sulfate, with a zinc salt concentration of 0.01-0.1 mol / L and a sodium dodecyl sulfate concentration of 0.001-0.005 mol / L. The hydrothermal reaction temperature is 75-110℃ and the time is 2-6 h. The zinc salt is zinc nitrate or zinc sulfate; the morphology control agent is sodium citrate or disodium hydrogen phosphate, and the molar ratio of the morphology control agent to the zinc salt is 1:5 to 1:1; the pH value is adjusted using ammonia water; the washing method is alternating soaking and washing with deionized water and anhydrous ethanol.
5. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, In step four, the weakly alkaline buffer solution has a pH of 8.0-9.0 and a concentration of 10-50 mmol / L, and the dopamine hydrochloride concentration is 1-3 mg / mL. The concentration of core-shell nanoparticles is 2-5 mg / mL, the reaction temperature is 20-30℃, and the reaction time is 12-24 h; the buffer solution is a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution; the co-deposition is an oscillating reaction.
6. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, In step five, the mass fraction of the chitosan quaternary ammonium salt aqueous solution is 0.5%-2.0%, the reaction temperature is 40-60℃, and the reaction time is 2-4h; the molecular weight of the chitosan quaternary ammonium salt is 50,000-200,000.
7. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, In step three, the aforementioned Nanosheet arrays The nanosheets have a thickness of 10-60 nm and a lateral dimension of 200-1200 nm.
8. The method for preparing a polyester antibacterial fabric according to claim 1, characterized in that, The The outermost titanium dioxide layer of the core-shell nanoparticles is 10-30 nm thick and is anatase.
9. A polyester antibacterial fabric, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
Citation Information
Patent Citations
Photocatalytic material for efficiently removing high-concentration nitrate through photocatalysis as well as preparation method and application of photocatalytic material
CN111974385A
Antibacterial agent and preparation method and application thereof
CN113802382A